Dogs with advanced myxomatous mitral valve disease have evidence of gastrointestinal bacterial translocation and systemic inflammation - Maria C. Jugan; Gabrielle A. Rands; Joerg M. Steiner; Natalia Cernicchiaro; Matthew C. Tanner; Lillian M. Novotny (PLoS ONE, 2025)
This study aimed to explore the potential relationship between the severity of cardiovascular disease and evidence of gastrointestinal bacterial translocation with systemic and cardiac inflammation in dogs with myxomatous mitral valve disease (MMVD). Thirty-six client-owned dogs, including 25 dogs with American College of Veterinary Internal Medicine Stage B1 or B2 disease but without increased left atrial pressure (Group 1) and 11 dogs with stage B2 disease with increased left atrial pressure or stage C disease (Group 2), were enrolled prospectively with an echocardiographic diagnosis of untreated MMVD. Serum lipopolysaccharide (LPS), interleukins (i.e., IL-2, IL-6, IL-8), tumor necrosis factor-alpha, and cardiac troponin were measured at enrollment. Presence of gastrointestinal clinical signs, fecal scores, body condition score, and muscle condition score were recorded. Linear regression models were used to compare LPS and inflammatory biomarkers based on MMVD severity. Spearman’s correlation was used to evaluate possible associations between inflammatory markers and LPS. The Fisher Exact test was used to compare proportions of dogs with gastrointestinal signs between Groups 1 and 2. Twenty percent of dogs in Group 1 had gastrointestinal clinical signs compared to 66.7% in Group 2 (P < 0.0001). Serum IL-6 (P = 0.037) and LPS (P = 0.024) concentrations were significantly associated with MMVD stage severity. Serum LPS and IL-6 were positively correlated (r s = 0.81; P < 0.0001). This study indicates that dogs with MMVD have evidence of loss of gastrointestinal barrier function as evidenced by bacterial translocation as the disease progresses in severity, which may be associated with systemic inflammation. These findings warrant further evaluation of gastrointestinal barrier function and maybe even the gastrointestinal microbiome as therapeutic targets in dogs with MMVD.